An Investigation on Effects by Adding Cerium and Lithium on Mechanical and Metallurgical Properties of AZ91D + XCe + XLi Cast Mg Alloy - R. Krishnan; S. Manivannan; A. Daniel Das; C. Ramesh Kannan; Bashyam Sasikumar (Advances in Materials Science and Engineering)
In this research work, the analysis of mechanical and metallurgical properties of AZ91D + XCe + XLi cast magnesium (Mg) alloys in adding cerium (Ce) and lithium (Li), where X can be varied. The destructive tests viz. mechanical test, tensile strength test, and microhardness test are used to investigate mechanical properties of AZ91D alloy in adding various weight percentages viz. 0.5, 1, 2, of Ce and Li. This result of this present investigation reveals that there will be refinement of grain size on AZ91D alloy in adding Ce and Li. The formation of second phase Al2Ce that has superior melting point, changes the distribution of the phase Mg17Al12 from a continuous network morphological transition to a tiny and dispersive distribution along the grain boundary. Furthermore, adding Li to the AZ91D magnesium alloy lowers the corrosion current density in a 3.5 percent NaCl solution, improving the alloy’s corrosion resistance. The results show that the AZ91D magnesium alloy, which contains 0.5 percent Ce + 1.0wt.%, outperforms other magnesium alloys.